Implementasi Penyajian Laporan Keuangan Entitas Non Laba Ditinjau Dari Interpretasi Standar Akuntansi Keuangan No.35 (Isak 35): (Studi Pada Mts Al-Kautsar Boarding School Sidoarjo) - Fifin Tasyfiyatur Ruchiyah; Maulidah Narastri (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study is aimed to define consistency in financial reporting which discussed about preparation and presentation of financial statements, the components of financial statements according to ISAK 35 only. Its consist of: cashflow, notes, and postion. This research is qualitative research. Data are collected by interviews and observations..Analysis process consisting of reduction data, presentation data and conclusions. The result show that the report doesn’t obey ISAK 35 yet.